2010
DOI: 10.1007/s10495-010-0511-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of the ribosomal protein S19 C-terminus in Gi protein-dependent alternative activation of p38 MAP kinase via the C5a receptor in HMC-1 cells

Abstract: We have demonstrated that an alternative C5a receptor (C5aR) ligand, the homodimer of ribosomal protein S19 (RP S19), contains a unique C-terminus (I(134)-H(145)) that is distinct from the moieties involved in the C5a-C5aR interaction. To examine the role of I(134)-H(145) in the ligand-C5aR interaction, we connected this peptide to the C-terminus of C5a (C5a/RP S19) and found that it endowed the second binding moiety of RP S19 (L(131)DR) with a relatively higher binding affinity to the C5aR on a human mast cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…Recombinant C5a (or peptide analogs) bearing the C-terminal protein of S19 also assume this dual activity Oda et al, 2008). S19 appears to bind to the second C5a receptor, the C5a 2 receptor, but this does not explain the dual activity (Nishiura et al, 2010b), proposed to be due to a diminution of Ga i coupling to the C5a 1 receptor in neutrophils by an as yet unidentified cofactor (Nishiura et al, 2011).…”
Section: Structure Of Complement Peptidesmentioning
confidence: 90%
See 1 more Smart Citation
“…Recombinant C5a (or peptide analogs) bearing the C-terminal protein of S19 also assume this dual activity Oda et al, 2008). S19 appears to bind to the second C5a receptor, the C5a 2 receptor, but this does not explain the dual activity (Nishiura et al, 2010b), proposed to be due to a diminution of Ga i coupling to the C5a 1 receptor in neutrophils by an as yet unidentified cofactor (Nishiura et al, 2011).…”
Section: Structure Of Complement Peptidesmentioning
confidence: 90%
“…Assuming a regulatory interplay of the C5a 2 receptor with the C5a 1 receptor, as they had already hypothesized earlier (Gerard et al, 2005), the investigators showed that two putative signaling events downstream of b-arrestin 1, ERK1/2 activation and chemotaxis, are enhanced after antibody blockade of the C5a 2 receptor. However, it remains to be confirmed that b-arrestin 1 mediates C5a 1 receptor-induced functions in human primary cells or transfected cells, as they may as well result from G protein activation (Buhl et al, 1994;Nilsson et al, 1996;Haribabu et al, 1999;Schraufstatter et al, 2009;Nishiura et al, 2010b;). In summary, there are credible indications of an active signaling function of the C5a 2 receptor involving b-arrestin, but further confirmation should be aimed at elucidating how this modulates the cellular response to C5a.…”
Section: A Introductionmentioning
confidence: 99%
“…C5aR2 is also a member of the GPCR family that binds to C5a; however, its role in C5a-mediated signaling and inflammation has been controversial (33). Previous studies have characterized the roles of C5a and C5aR1 in the human and murine models of mast cells, but the majority of these studies have been performed using either mast cell lines transfected to express C5aR1 (46), immature mast cell lines (47,48), mucosal-type mast cells such as BMMCs with no endogenous C5aR1 (22), or C5aR1-deficient mice (11) and they present inconsistent data. Nevertheless, the general consensus is that C5a activates only MCTC (20).…”
Section: Discussionmentioning
confidence: 99%
“…The RP S19 polymer binds to the monocyte C5aR and shifts a Gβγ subunit-dependent downstream signal from ERK1/2 pathway to p38 mitogen-activated protein kinase (p38MAPK) pathway independent of intracellular (endoplasmic reticulum) calcium release [39]. The p38MAPK signal is artificially produced by C5a stimulation following simultaneous treatment with phosphatidylinositol 3-kinase and PLC inhibitors (LY294002 and U73122) at concentrations equal to half of their respective IC 50 values.…”
Section: An Alternative Signal Transduction Pathway Mediated By the Mmentioning
confidence: 99%
“…The LFA-1 functions as an adhesion molecule, binding to intercellular adhesion molecule 1 on antigen-presenting cells for promoting proliferation/differentiation of T cells. We are interested in the different signal transduction pathways mediated by the same LFA-1 but in a cell type-specific manner, as previously shown for the C5aR [39,48]. It is very complicated, because the oral manifestation appears to change with the type and quantity of bacteria in a circadian rhythm.…”
Section: The C5ar In Periodontitismentioning
confidence: 99%